The outside man - Bentley, Don (Bentley, Don. Matt Drake thriller, 2021)
"The fight for freedom has sent Matt Drake to some of the world's most dangerous spots. This time the war is coming to his front door. Broad daylight on an Austin, Texas, street and DIA agent Matt Drake is fighting for his life against a highly trained team of assassins. Who are they? Why do they want him dead? How will he protect those closest to him? The answers will take him into some of the most dangerous spots in the Middle East and will put him in the clutches of an old foe known simply as the Devil. It's a world of double crosses, with no boundaries between the guilty and the innocent. It will take all of Drake's wiles to get out alive."--Provided by publisher.